An assessment of the association of taurodontism with various dental anomalies, syndromes, systemic diseases and/or genetic diseases, and its role in identification. Issue 5 (3rd September 2018) - Kirzioglu, Zuhal; Ceyhan, Derya; Gok Coban, Begum
Abstract: The aims of the study are to determine the association of taurodontism with numerical, dimensional, formal and structural dental anomalies, various syndromes, systemic diseases and/or genetic diseases, and to represent the clinical implications of the anomaly for clinicians and future forensic and genetic studies. The records of patients examined at the Department of Pedodontics, Faculty of Dentistry, Suleyman Demirel University were retrospectively analysed. A final sample of 837 patients with various dental anomalies, syndromes, systemic and/or genetic disorders was selected and evaluated to detect the presence of taurodontism. A chi-square goodness of fit test was performed to assess the distribution of this anomaly according to gender and localization. Further, Pearson's correlation coefficient was calculated. Taurodontism was detected in 199 patients. It was mostly encountered with tooth agenesis. The differences of the distribution of this anomaly between the upper/lower jaws were statistically significant. Bilateral taurodontism was more frequent than unilateral taurodontism and was mainly seen on the maxillary first molars. No statistically significant correlation was found between the missing and taurodont teeth. Identifying individuals with multiple dental anomalies and/or with the syndromes and systemic diseases could serve as a guide for further forensic and genetic studies.